2021
DOI: 10.3390/fluids6060215
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Bubble Cloud Break-Off Mechanisms at Micro-Channels

Abstract: This paper provides new physical insight into the coupling between flow dynamics and cavitation bubble cloud behaviour at conditions relevant to both cavitation inception and the more complex phenomenon of flow “choking” using a multiphase compressible framework. Understanding the cavitation bubble cloud process and the parameters that determine its break-off frequency is important for control of phenomena such as structure vibration and erosion. Initially, the role of the pressure waves in the flow developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To find the optimum mesh size for the given situation, a mesh independence study is carried out using Winklhofer's U-type geometry 45 by employing the fuel properties listed in Table I. The k − ω SST turbulence model with smooth wall conditions is used to extract the results for the mesh independence study.…”
Section: Mesh Independence Studymentioning
confidence: 99%
“…To find the optimum mesh size for the given situation, a mesh independence study is carried out using Winklhofer's U-type geometry 45 by employing the fuel properties listed in Table I. The k − ω SST turbulence model with smooth wall conditions is used to extract the results for the mesh independence study.…”
Section: Mesh Independence Studymentioning
confidence: 99%
“…When the formed vapor structures collapse violently, the surface energy is conserved and influences the evolution of the surrounding surfaces. 3,6 First, the conserved energy further augments the collapse of other vapor cavities from the shock that is caused within the structure which is due to the bubbly mixture leading to a reduced speed of sound. 6,7 Second, this energy is also transported downstream the nozzle exit where it influences the surface breakup of the atomization process.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 First, the conserved energy further augments the collapse of other vapor cavities from the shock that is caused within the structure which is due to the bubbly mixture leading to a reduced speed of sound. 6,7 Second, this energy is also transported downstream the nozzle exit where it influences the surface breakup of the atomization process. 3 Third, the energy that is conserved from the violent collapse also causes material erosion and inevitable failure of the injector.…”
Section: Introductionmentioning
confidence: 99%
“…The cavitation in the cavitation ring grew rapidly near the nozzle and decreased gradually. Paul McGinn et al [20] studied the role of the pressure wave in the flow development and found that the dynamics of the pressure wave determined the dynamic characteristics of the bubble cloud under the condition of "choking". Ruolong Ma et al [21] proposed a model that provides a prediction of the resonator pressure fluctuations based on the thickness of the approach boundary layer, the free stream speed and the acoustic properties of the resonator.…”
Section: Introductionmentioning
confidence: 99%